Dynamics of soil formation factors and their influence on agricultural technology in the Kamennaya Steppe - V. A. Isaev; V. P. Belobrov; A. L. Ivanov (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The analysis of long-term observations in the Kamennaya Steppe (over 125 years) for climatic parameters (air temperature and precipitation), ground water level, vegetation species composition revealed the main trends in their variability. Since 1969 there has been an increase in temperature and a reduction in temperature fluctuation during the year. Over the last 30 years, the difference has reached 1.90, and over the last decade it has grown by 0.40 due to the cold season. The amount of precipitation over the same 50-year period has not changed much. In total, an increase of 45 mm was observed over the decade (1999-2008). In the XXI century, there has been registered an increase in the amount of precipitation in the cold season by 12.7% and a decrease in the warm season, which creates certain prerequisites for climate continentality mitigation during the annual cycle. During the first 70 years of observations, the groundwater level in the well No. 1 was on average at the depth of 6.5 m (5.7-7.3 m). At the end of the XX century and at the beginning of the XXI century, there was marked a pronounced rise in the ground water level, the average depth was 3.8 m, which coincided with the growth of average annual temperature and an increase in total rainfall. In this period changes in the long-term regime of ground and surface soil moisture resultedin expanding the area of wetlands and hydromorphic soils on the territory of the steppe. The period of 2009-2018 is characterized by a continued increase in average annual temperatures and a decrease in precipitation, which may lead to a seasonal change in temperature and precipitation to milder and wetter winters and warmer and drier summers. Transformation of vegetation for 100 years of observations had several stages with a general trend to change the steppe grasslands to meadow-steppe, shrubs and woody species.